Transformation of Death in Postmodern Russian Fairy Tale Retellings - Barbora Vinczeová; Ruslan Saduov (Funes)
This paper focuses on the changes in the traditional character of death – Koschei the Deathless – retrieved by Catherynne Valente from the Russian fairy tales and incorporated in her novel Deathless (2011). As a postmodern fairy tale reinterpretation, the novel supplies a modified plot along with the substantial changes in fairytale characters. In particular, this paper observes how the character of death changes from a black-and-white villain to a complex, morally ambiguous protagonist. Literary analysis and comparison focuses on several points such as romanticising and humanizing death, change of its function and purpose, as well as adding political criticism.